2014
DOI: 10.1016/j.jsps.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacists: Bridging the gap between patients and physicians

Abstract: The clinical pharmacy has spread out drastically in terms of its professional services throughout the past few years. The clinical pharmacist become a crucial element of healthcare team and promotes patient care by interacting with physician and patient. The aim of this paper is to highlight the role of clinical pharmacists in various departments. It concludes that the features of interactions occurring between clinical pharmacists and physicians influence the teamwork between pharmacists and physicians and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 2 publications
0
47
0
1
Order By: Relevance
“…In this regards, adequate information or patient counselling must be supplied in addressing potential fears or stigmas associated with chemotherapy and hence increase adherence to the given treatment [27] . On the other hand, integrating pharmacist into the primary health care system has been increasingly recognized as a means to manage complex medication needs, reduce drug costs, length of hospital stay and improve economic outcomes [25,28] . The role of pharmacist has been diversified from medication centred to patient centred care [29] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regards, adequate information or patient counselling must be supplied in addressing potential fears or stigmas associated with chemotherapy and hence increase adherence to the given treatment [27] . On the other hand, integrating pharmacist into the primary health care system has been increasingly recognized as a means to manage complex medication needs, reduce drug costs, length of hospital stay and improve economic outcomes [25,28] . The role of pharmacist has been diversified from medication centred to patient centred care [29] .…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that pharmacist involvement was well accepted with high satisfactory score by both the patient and physicians [25,30] . In oncology setting however, the role of the pharmacist is rather in an imbalance, which deals with compounding of the drug, calculation of body surface area of patients and communication to the prescriber [26,28] . Limited activity has been focused on cancer patient-centred care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grande parte dos erros de medicação é atribuída à equipe de enfermagem por atuar diretamente nas últimas etapas de preparo e administração de medicamentos 6 , no entanto o farmacêutico inserido na equipe assistencial deve detectar estes erros no início ou no meio do sistema, intervir e corrigir possíveis danos 7 . A análise da prescrição é uma das atividades atribuída ao profissional farmacêutico clínico, intervindo em situações como: reconciliação medicamentosa; forma farmacêutica, via de administração, posologia e administração inadequadas; incompatibilidades entre medicamentos; estabilidade e diluição de medicamentos inadequadas; bem como evitar que o paciente alérgico a determinado medicamento seja prescrito 8,9 . Com isso, o objetivo do estudo foi identificar e quantificar o número de intervenções farmacêuticas realizadas em pronto atendimento em um hospital de ensino.…”
unclassified